Early Predictors of Learning a Foreign Language in Pre-school – Polish as a First Language, English as a Foreign Language - Łockiewicz, Marta; Sarzała-Przybylska, Zuzanna; Lipowska, Małgorzata (Frontiers in Psychology, 2018)
When a foreign language acquisition begins in preschool, at which time young learners are particularly linguistically sensitive, it allows for a higher foreign language competence in future. Moreover, a second language learning depends on a learner’s aptitude. The aim of our study was to assess the early predictors of learning English as a Foreign Language in Polish preschool students who had not yet started formal literacy instruction, and to characterize the level of their oral receptive and active skills in English. 30 children aged between 3 years 5 months and 5 years 10 months who attended two private and one state kindergarten, participated in the study. All were native speakers of Polish, and apart from English classes, communicated in their first language at kindergarten and in their everyday life. Nonverbal intelligence, emerging literacy, phonological awareness in Polish, and knowledge of English were assessed. We found that in Polish pre-school children emerging letter identification from their first language alphabet, phonological awareness in their first language, and nonverbal intelligence were related to the achievements in learning English as a foreign language, despite the differences in transparency between the two languages. Moreover, the children’s passive color vocabulary was larger than their active vocabulary, and they were used to repetition tasks. The participants in our study attempted to communicate in English during the assessment, which suggests that even at a pre-school age they were able to differentiate between first language and foreign language discourse. We also identified some problems possibly stemming from linguistic transfer, like articles omissions. Therefore, teachers should pay more emphasis to the differences between the first and the second language, in terms of: syntax, morphology, phonetics, phonology, and orthography, to prevent later consolidation of early errors The automatisation of correct linguistic habits in young learners would equip them with skills for their later foreign language educational success.